Demand Forecast of NFC Mobile Users – A Case Study of Serbian Market - Stanivuković, Bojan; Radojičić, Valentina; Marković, Dejan; Blagojević, Mladenka (Promet - Traffic&Transportation, 2018)
Near Field Communication (NFC) is a very short-range type of radio communication that is compatible with other contactless communication technologies. It provides enormous possibilities, particularly given that it does not require any particular communication infrastructure. NFC technology has found possible application in contactless cards and mobile phone devices as a communication infrastructure which provides a platform for the development of NFC-based business services. This paper proposes a novel approach to forecasting the number of new users of NFC mobile phones based on fuzzy logic and the Norton-Bass diffusion model. The proposed approach is demonstrated through the case study.